Public Service Digital Transformation Model In Supporting The Development Of A New Suro Village, Suro Makmur District - Darliansyah, Darliansyah; Abdiyanto, Abdiyanto; Rusiadi, Rusiadi; Novalina, Ade; Nazliana Nasution, Lia; Suhendi, Suhendi (Publisher Cv. Inara, 2022)
The purpose of this study is to predict the increase in development and public services in Suro Baru Village, Suro Makmur District based on the SEM model. The analytical model used in Structural Equation Modeling (SEM) . Questionnaire data analysis will be processed using the SEM method with the IBM-SPSS-AMOS program. The results of the study show that 1) technology directly has a positive influence and significant to development in Suro Baru Village, Suro Makmur District, Aceh Singkil Regency. 2) Directly, infrastructure facilities have a positive and positive influence significant to development in Suro Baru Village, Suro Makmur District, Aceh Singkil Regency. 3) The potential has no influence on public services in Suro Baru Village, Suro Makmur District, Aceh Singkil Regency. 4) Directly technology has a positive influence and significant to public services in Suro Baru Village, Suro Makmur District, Aceh Singkil Regency. 5) Directly, infrastructure facilities have a positive and positive influencesignificant to public services in Suro Baru Village, Suro Makmur District, Aceh Singkil Regency. 6) Directly the potential to have a positive and significant influence on public public services in Suro Baru Village, Suro Makmur District, Aceh Singkil Regency. 7) Indirectly technology has a positive influence and significant to public services through development in Suro Baru Village, Suro Makmur District, Aceh Singkil Regency. 8) Indirectly, infrastructure has a positive and positive influence significant to public services through development in Suro Baru Village, Suro Makmur District, Aceh Singkil Regency. 9) Indirectly the potential to have a positive and significant influence on public public services through development in Suro Baru Village, Suro Makmur District, Aceh Singkil Regency.